Shuri (Black Panther novel, 1,, 2023)
From New York Times bestselling author Nic Stone comes an all-new upper middle grade series based on one of the Marvel Universe's break-out characters Shuri, from Black Panther! An original, upper-middle-grade series starring the break-out character from the Black Panther comics and films: T'Challa's younger sister, Shuri! Crafted by New York Times bestselling author Nic Stone. Shuri is a skilled martial artist, a genius, and a master of science and technology. But, she's also a teenager. And a princess. This story follows Shuri as she sets out on a quest to save her homeland of Wakanda.For centuries, the Chieftain of Wakanda (the Black Panther) has gained his powers through the juices of the Heart-Shaped Herb. Much like Vibranium, the Heart-Shaped Herb is essential to the survival and prosperity of Wakanda. But something is wrong. The plants are dying. No matter what the people of Wakanda do, they can't save them. And their supply is running short. It's up to Shuri to travel from Wakanda in order to discover what is killing the Herb, and how she can save it, in the first volume of this all-new, original adventure.